IDENTIFIKASI TELUR Ascaris lumbricoides DENGAN MENGGUNAKAN PEWARNAAN TRICHOROME - Darmadi Darmadi; Eli Yusrita; Nadia Rahmadhani (LPPM Universitas Abdurrab, 2023)
The trichrome staining technique on stool specimens is a modification of the Gomori staining technique and has since been used as a diagnostic tool for the identification of intestinal parasites. The purpose of this examination was to determine the morphology of Ascaris lumbricoides using trichrome staining. The faecal examination method used is the direct preparation method by dropping the stool specimen on a glass slide which is then stained with trichrome or 2% Eosin and then covered with a cover slip, after which it is examined under a microscope. The results of trichrome staining on the color and morphology of worm eggs were better than using 2% Eosin. In trichrome staining made of 4 preparations, fertilized eggs were found with an oval shape, measuring 45 - 75 microns long and 35 - 50 microns wide, with a bright green background, giving the eggs a brownish yellow color with a dark green coating, so that the parts of the egg are clearly visible, while in Eosin 2% it gives a brownish red color to the egg and has a contrasting red background so that the parts of the egg are rather difficult to distinguish.